Analysis of Toyibalun Customs in Society in the Perspective of Islamic Economics (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the implementation of the Toyibalun traditional custom among the people of South Bolaang Mongondow and to examine its values from the perspective of Islamic Economics. Using a field research approach with a descriptive qualitative method, data were obtained through interviews, observations, and document studies. The findings show that the Toyibalun custom is a tradition rich in social, cultural, and spiritual values. The process involves several stages, from family deliberations to the presentation of household items, symbolizing familial bonds and marital commitment. This tradition serves as a form of cultural heritage preservation amid social change. From the perspective of Islamic Economics, Toyibalun reflects responsibility, justice, and balance between husband and wife in accordance with Islamic teachings. The presentation of household items is not merely a ritual but a symbol of sincerity and moral responsibility in building a harmonious family. This tradition illustrates the harmony between local cultural values and the principles of Islamic Economics.